Does the Guided Inquiry Model Improve Student's Problem Solving Thinking Ability? Meta-Analysis - Joko Widodo; Loso Judijanto; Abdul Halim; Azhariah Rachman; Sutarto Sutarto; Tomi Apra Santosa (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to investigate the effectiveness of guided inquiry models to improve students' problem-solving abilities. This type of research is a meta-analysis.Â  The inclusion criteria in research are publications from reputable international journals and proceedings; Research must be experimented with guided inquiry learning models and conventional control class models; Research obtained from google scholar database; Hindawi, ScienceDirect, ERIC and IEEE; research related to guided inquiry and problem solving models; The study was published in 2013-2023 and the study had a sample size (N), mean value and standard deviation (SD). The results of the analysis of 18 studies suggest that there is a significant influence of guided inquiry models on problem-solving ability (Z = 9.29; p < 0.001; 95 % Confidence Interval [0.581; 1.245]. Effect size criteria are high with (rRE= 0.849]. This finding explains that the guided inquiry model has a significant effect on students' problem-solving abilities